Tools to Increase the Effectiveness of the Company in the Field of Digital Economy Skills - Sharafutdinova, N.; Palyakin, R. (International Journal of Criminology and Sociology, 2022)
The article suggests a mechanism for increasing the effectiveness of online education in modern conditions to increase digital economy skills. The purpose of this study is to identify performance indicators of online education and offer recommendations for the development of online educational business. To achieve this goal, the article provides an overview of trends in online education. The role of modern tools for managing and implementing the online educational process is noted. The types of efficiency levers in business are considered. The limit of the effectiveness of levers in online education is determined. The algorithm for managing the effectiveness of online education is based on efficiency levers. Data on the effectiveness of levers of online education efficiency are provided. The possibilities of using various efficiency levers to increase the company's competitiveness in online education are discussed.